1996
DOI: 10.1002/art.1780391006
|View full text |Cite
|
Sign up to set email alerts
|

Two major autoantigen—Antibody systems of the mitotic spindle apparatus

Abstract: Objective. To characterize human autoantigenantibody systems related to the mitotic poles and spindles.Methods. Thirty-seven human sera with autoantibodies staining mitotic poles and spindles in indirect immunofluorescence (IIF) studies were further characterized by immunofluorescence on mitotic cells and by immunoblotting and immunoprecipitation. Clinical diagnoses meeting the American College of Rheumatology criteria were based on chart review and interview with the corresponding physicians.ResuUs. Two autoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
8

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 58 publications
2
42
0
8
Order By: Relevance
“…In addition t o these antigens, which appear to b e integral components of the centrosome, the intranuclear protein NuMA (nuclear protein associated with the mitotic apparatus) is distributed t o daughter cells following cell division through its transient association with the centrosome (6)(7)(8). N u M A is an autoantigen that has been found to be frequently associated with Sjogren's syndrome (9).…”
mentioning
confidence: 99%
“…In addition t o these antigens, which appear to b e integral components of the centrosome, the intranuclear protein NuMA (nuclear protein associated with the mitotic apparatus) is distributed t o daughter cells following cell division through its transient association with the centrosome (6)(7)(8). N u M A is an autoantigen that has been found to be frequently associated with Sjogren's syndrome (9).…”
mentioning
confidence: 99%
“…Based on the comparison of molecular weights and staining patterns, it became obvious that MA-I1 may be identical to HsEgS, 'while MA-I is the more abundant and well-characterided NuMA. To verify this correlation, we obtained 4 sera with MA-I1 activity from Dr. E. and colleagues that appears elsewhere in this issue of Arthritis and Rheumatism (27), MA-I was confirmed to be NuMA. These findings support our conclusion that NuMA and HsEgS are the predominant antigens responsible for the MSA pattern.…”
Section: Discussionmentioning
confidence: 75%
“…It is therefore unlikely that the immune response is merely directed to crossreactive coiled-coils in these proteins. In addition, coiled-coils have been noted in many other non-Golgi autoantigens including nuclear mitotic apparatus protein NuMA [32,33], lamin B [34,35], myosin heavy chain [36], 52 kDa SS-A/Ro [37], and 70/80 kDa Ku antigens [38,39]. Our laboratories have collected and characterized human anti-Golgi sera by immunoblotting and immunoprecipitation over the past few years and in addition to the identified Golgi autoantigens reported, it was observed that many AGA sera recognized unidentified Golgi proteins (unpublished).…”
Section: Distinct Autoimmune Responses To Golgin-67mentioning
confidence: 98%